Influence of ownership structure and international operations on web-based environmental disclosure in the Asian mining industry - Muhammad Hamdan Sayadi; Doddy Setiawan (Sustainable Futures)
Based on the stakeholder theory, this research explores the influence of various forms of stakeholder pressure on web-based environmental disclosure within the Asian mining industry. This paper included all mining companies listed on the capital markets of Asian countries that showed strong motivation as they obtained higher recognition and demand among investors and the general public. In total, 202 mining companies met the specified criteria in Asia. However, 67 mining companies were excluded as they either not having resourceful website or had websites that were not accessible in English. The study's findings reveal that both government and institutional exert a positive and significant impact on the extent of web-based environmental disclosure. Similarly, international operations are closely linked to the scope of web-based environmental disclosure. Thus, the outcomes of this research contribute to a more comprehensive understanding of the factors determining web-based environmental disclosure, bridging a gap left by prior research which predominantly focused on company characteristics.